Batch and Column Extraction of Lead from Al-Doura Oil Refinery Soil - Gzar, Dr. Hatem Asal; Gatea, Israa Mohammed (Journal of Petroleum Research and Studies, 2017)
The aim of this research is to investigate the extraction of lead (Pb) from soil of Al-Doura oil refinery in Baghdad/Iraq. Ethylenediaminetetraacetic acid disodium salt (Na2EDTA) and Hydrochloric acid (HCl) solution were used as extractants. Soil washing method was practiced in two ways, batch extraction and column extraction experiments. A set of batch experiments were carried out at different conditions of extractant (Na2EDTA, HCl) concentration, contact time, pH and agitation speed. From the batch experiments, the maximum removal percentages of Pb that have been obtained were 70 % using Na2EDTA (0.1M) at pH 4 , agitation speed 200 and at equilibrium time 4 hours and 65 % using HCl (1M) at pH 1.08 , agitation speed 200 at equilibrium time 5 hours. Column experiments were conducted at different conditions of extractant (Na2EDTA, HCl) concentration, contact time and flow rate. The maximum removal percentages of Pb were 78% using Na2EDTA (0.1M) at pH 4 , flow rate 30 ml/hr and equilibrium time 8 hours and 75% using HCl (1M) at pH 1.08, flow rate 20 ml/hr and equilibrium time 10 hours. The column extraction proved that the extractant volume required to achieve high removal efficiency is less than that of the batch extraction, but requires a longer contact time. The experimental data of batch and column extraction were applied in four kinetic models; first order, parabolic diffusion, two constant and Elovich model to find best fit model for extraction system. For batch extraction, the parabolic diffusion and two-constant models gave the best correlation {coefficient of determination (R2)} with experimental data using HCl and Na2EDTA respectively. While for column extraction, Elovich model gave good correlation with experimental data.